Secondary Adjustment in Prisons: Prisoners’ Strategies of Influence - Khiat, Henry (Qualitative Sociology Review, 2010)
This participant observation research explores and examines the strategies that prisoners use to influence prison officers in an Asian prison setting. Grounded theory methodology is employed in the analysis process. From the study, eight strategies of influence are conceptualised: repetition, distraction, finding excuses, feigning ignorance, false compliance, hearsay, direct hit and spontaneous protest. They are further subsumed under three main categories of Enhancers, Trouble Shooters and Resistors. On the other hand, there are three categories of prison officers with respect to their responses to the eight strategies of influence – Idealists, Pragmatists and Authoritarians. In summary, this study serves three objectives. First, it provides a fresh perspective on how prisoners attempt to influence prison officers in their daily interactions. Second, it has demonstrated that data collection through covert participant observation can be done effectively without causing any harm to the stakeholders in a prison setting. Lastly, this study has implications for the development of theory, practice and future research in the area of penology.